Tatalaksana Pasien Skabies Dengan Pendekatan Kedokteran Keluarga Management Efforts For Scabies Patients With Family Medicine Approach - Nadia Karimah; Noviana Zara (Lembaga Pengembangan Kinerja Dosen, 2024)
Patient An K was brought by her parents to the MTBS clinic of Puskesmas Kuta Makmur with complaints of itching throughout the body since 1 month ago. Complaints are mainly felt in the area between the fingers, toes and in the folds of the neck, which are getting worse at night. The patient's parents conveyed that their child's complaints had repeatedly appeared since 3 months ago, as well as a history of other family members who also had the same complaints. The patient tried to buy his own medicine at the pharmacy or was taken to the orderly but the complaints returned and did not decrease. From the examination results obtained HR: 89x/i, RR: 19x/i, temperature: 36,5C. Primary data was obtained through alloanamnesa and physical examination by conducting home visits, filling out family folders, and filling out patient files. Assessment was carried out based on holistic diagnosis at the beginning, process, and end of the visit quantitatively and qualitatively. The interventions carried out included education about the causes of scabies to the family, environmental sanitation and hygiene education and management of the disease and explaining the complications that might arise from the patient's disease so that the patient's family would maintain personal hygiene and environmental cleanliness.